PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP KUALITAS LABA PADA PERUSAHAAN KONTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Nur Aini; Suprihatin Suprihatin; Indra Lila Kusuma (CV. Denasya Smart Publisher, 2024)
This research aims to determine the effect of profitability, leverage, and liquidity on the quality of profits in construction and building companies listed on the Indonesia Stock Exchange (BEI). This research uses quantitative methods. The population used in this research is the annual financial reports of construction and building companies listed on the Indonesia Stock Exchange (BEI) for 2018-2022, totaling 22 companies. The sample in this research used purposive sampling with certain criteria. The results of this research show that in the partial test, profitability has a negative and significance effect on earnings quality. Leverage has a negative and significance effect on earnings quality and liquidity has a negative and significance effect on earnings quality.